2010
DOI: 10.1007/s10526-010-9271-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of heat and desiccation tolerance in Heterorhabditis bacteriophora through cross-breeding of tolerant strains and successive genetic selection

Abstract: Genetic selection can be a powerful tool to increase beneficial traits in biological control agents. In this study the heat and desiccation tolerance of the entomopathogenic nematode Heterorhabditis bacteriophora Poinar (Rhabditidomorpha: Strongyloidea) were significantly increased by cross breeding tolerant parental strains and successive genetic selection. These strains originated from a prior screening among 60 strains for increased stress tolerance. During genetic selection, the selection pressure was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…The H. bacteriophora hybrid strains (Table 1) had been produced within the study reported by (Mukuka et al 2010c). The virulence and reproduction potential was compared with the hybrid strain EN 01, which is the commercially used strain of e-nema GmbH (Schwentinental, Germany).…”
Section: Nematode Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The H. bacteriophora hybrid strains (Table 1) had been produced within the study reported by (Mukuka et al 2010c). The virulence and reproduction potential was compared with the hybrid strain EN 01, which is the commercially used strain of e-nema GmbH (Schwentinental, Germany).…”
Section: Nematode Strainsmentioning
confidence: 99%
“…Penetration into G. mellonella was always less than 20%, however, significant differences were recorded (F = 4.08; Table 1 Description of hybrid strains, their mean tolerated temperature (°C) and/or water activity (a w ) after adaptation or without prior adaptation before exposure to stress conditions according to Mukuka et al (2010c) and mean ranking of fitness according to results presented in Table 2 Strain The highest penetration was recorded for HA1 (17.7%) followed by H3 (17.1%) and then DD2 (16.1%). The lowest number of penetrated DJs was recorded for the commercial strain EN01 (4.6%), although not significantly different from HH1 (6.2%), DA1 (7.1%), D3 (7.7%) and HD4 (9.6%) (Fig.…”
Section: Host Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also several formulation types that contain different media and have different storage durations (Grewal, 2000). Recent studies have generally focused on the effectiveness of EPNs on different insect pests and the improvement of several characteristics with genetic studies, such as selective breeding or hybridization (Mukuka et al, 2010a(Mukuka et al, , 2010cNimkingrat et al, 2013;Susurluk et al, 2013;Ulu & Susurluk, 2014). At present, one of the major obstacles in EPN commercialization is the high application cost due to short shelf life and high production expenses.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the optimal temperature for EPNs is approximately 25 °C; however, some strains can handle temperatures up to 40 °C without any adaptation, or genetic selection (Koppenhöfer, 2000;Ulu & Susurluk, 2014). Several studies have achieved improvement in these characteristics with hybridization (Mukuka et al, 2010a). For a commercial EPN strain, higher heat tolerance alone may not be enough.…”
Section: Introductionmentioning
confidence: 99%